MEMPELAJARI PENGARUH PERBANDINGAN TERIGU DAN UBI JALAR UNGU (Ipomoea batatas var ayamurasaki) TERHADAP KARAKTERISTIK BAKPAO - Ayu, Yohana Christiani; Ina, Putu Timur; Ekawati, IG Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 2 No 1 (2013): Jurnal ITEPA, 2013)
The aims to investigate the effect of comparisons of wheat with purple sweet potato on the characteristics of “bakpao” and determine rate comparison of wheat with purple sweet potato with the best characteristics of “Bakpao”. The method of the research used Randomized Block Design by treatment of the comparisons of wheat with purple sweet potato it consisted six levels such as 1) (100% : 0%); 2) (90% : 10%); 3) (80% : 20%); 4) (70% : 30%); 5) (60% : 40%) and 6) (50% : 50%). Each treatments was repeated 3 times to obtain 18 units, the datas were analyzed by analysis of variance. If there were any effect of the treatment, the analysis followed by Duncan's Multiple Range Test. The results showed the comparisons of wheat with purple sweet potato a very significant effect on the moisture content, fat content, protein content, ash content, carbohydrate content, anthocyanin content, colour, flavor, taste, texture, and overall acceptance . Comparison of wheat with purple sweet potato at a rate comparisons of wheat 50% and purple sweet potato 50% produce the best characteristics with moisture content 41.181%, ash content 0.008%, protein content 10.220%, fat content 7.276%, carbohydrate content 41.314%, anthocyanin content 2.417 mg / 100g, colour : purple, flavour : rather like, taste : like, texture : soft and overall accepted : like.
Keywords: Wheat, Purple sweet potato, Characteristics, “Bakpao”